APAKAH ORANG KAYA DI DALAM GEREJA MEMBUTUHKAN PENDAMPINGAN PASTORAL? - Stimson Hutagalung (Fakultas Filsafat Universitas Advent Indonesia, 2015)
Community in the church is divided into three classes: top layercommunity, middle layer community and bottom layer community. A citizen of thetop layer community is not too many when compared with the middle layer andbottom layer communities in the church. The top layer or often called as rich peopleregards as people who already have everything and do not need any more to get theattention even from the church. But in reality they too are human beings with athousand problems in their lives. Church need to give attention and pastoral care notonly for the bottom and middle layers community but also for rich people who aremembers of the congregation.